‘The Chief and Principal Part of the Gospel’; Baptist Ecclesiology and the Authority of the Bible - Finamore, Stephen (2025)
This article argues that the beginnings of the Baptist movement cannot be fully understood without an awareness of how seriously it and other Separatist groups took the authority of Scripture. It discusses Baptist approaches to the interpretation of the Bible and the Baptist Union Declaration of Principle. It asserts that the churches should best understand themselves, their office holders and their structures in terms of the New Testament rather than in terms of their legal status or the understandings of them found in the social sciences.
Keywords: declaration of principle; Bible; Baptist